Association of dietary inflammatory indices with sarcopenia and all-cause mortality in COPD patients - Jiang, Qi; Ma, Zheru; Sun, Jing; Li, Yang (Frontiers in Nutrition, 2024)
Background: Sarcopenia often accompanies COPD but its impact on survival is unclear. We also lack evidence on how dietary pro-inflammatory capacity relates to sarcopenia in COPD.Methods: Using NHANES data from 1999-2006 and 2011-2018, we studied 1429 COPD patients. We analyzed the Dietary Inflammatory Index (DII) and sarcopenia prevalence, as well as the relationship between sarcopenia, muscle mass (ASMI), and mortality using logistic regression, Kaplan-Meier, and Cox models.Results: Higher DII scores correlated with female gender, unmarried status, lower education, and lower ASMI in COPD patients. Those in the highest DII quartile had a 2.37 times higher odds of sarcopenia. No non-linear DII-sarcopenia relationship was found. COPD patients with sarcopenia had significantly higher all-cause mortality. Sarcopenia was associated with a 44% higher risk of mortality. ASMI showed a non-linear relationship with mortality, with a turning point at 8.32 kg/m². Those above this threshold had a 42% lower mortality risk.Conclusion: Concurrent sarcopenia significantly increases mortality risk in COPD patients, and ASMI exhibits a non-linear association with mortality, with a critical threshold identified. DII is associated with sarcopenia incidence. Further research should explore dietary interventions to improve COPD prognosis.